Diversidad genetica en especies de Phaseolus - Hidalgo, R.; Song, L (International Center for Tropical Agriculture, 1979)
A report is given on the 4 cultivated species of the genus Phaseolus, studying geographic distribution, taxonomy and morphology, agronomic characteristics and germplasm collection. The areas where Phaseolus vulgaris is extensively cultivated are North, Central and South America, Europe and E. Africa. The differentiation among the 4 species are described according to seed type, germination, leaf characters, flowers and inflorescence, pod shape and size, determinate and indeterminate growth habits, changes in the characters of cultivated vs. noncultivated forms, adaptation of the 4 species and the objectives of research conducted on each one. Germplasm evaluation has been carried out since 1970 and includes ca. 800 selected materials. Tables and figures are presented, illustrating this information. (CIAT)